Analysis of Total Phenolic from a Root Tabar Kedayan - Siti Jubaidah; Henny Nurhasnawati; Heri Wijaya (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2019)
East Kalimantan has a diversity of plants from various Dayak ethnic groups. One of them is the Tabar Kedayan (Aristolochia foveolata Merr) plant located in Malinau district. This plant is empirically efficacious as antidiarrhea, antidotum (anti poison). Efficacy of Tabar Kedayan plant has not been scientifically confirmed, this is because there is still little scientific research and information about the content of secondary metabolites and bioactive compounds contained in Tabar Kedayan Root. The presence of secondary metabolite is phenolic which has considerable biological active prospects as antioxidant, antibacterial, antiamuba, anti-inflammatory, antihepatotoxic and antivirus. The aim of this research is to analyze the chemical content and total phenolic content of root tabar kedayan in fractionation with various nonpolar, semipolar and polar solvents. The analysis used in the determination of total phenolic content using visible spectrophotometric method. Data of analysis used standard curve method based on absorbance data and concentration of standard solution. The results of this study obtained the highest total phenolic average on ethyl acetate fraction of 77.74 ±2,633 mg GAE/g then ethanol fraction of water amounted to 38.10 ±0,461 mg GAE/g and the smallest level of n-hexane fraction of 29.36±0,193 mg GAE/g. Conclusions in this study total phenolic content is found in most semipolar fractions.